A repetência e a reprovação na escola graduada, em Minas Gerais, nas primeiras décadas do século XX - Fernanda Cristina Campos da Rocha (2017)
The aim of this research was to investigate the phenomena of school failure and retention, in Minas Gerais, in the first decades of the 20th century. This work is part of the studies on schooling history, mainly the creation of a new school culture in the state, based on graded school, in which these two phenomena are consolidated. Our interest was: to analyze the school practices of failure and retention, aiming to understand how they were thought and lived in a grupo escolar in Minas Gerais- the Grupo Escolar Paula Rocha, in the town of Sabará; to establish the relations between school time, prescribed in the education legislation, and the actual students trajectories; to identify the processes of evaluation and how they were applied, so as to understand students retention or approval for the next school year; and analyze the production and circulation of different discourses on the themes. So as to reach the proposed objectives, the corpus used was: educational legislation, teaching programs, reports from principals and inspectors, minutes from exams, promotion reports, enrollment books, Portuguese language dictionaries, the Revista do Ensino, and the Jornal Minas Geraes. The analytical approach was centered, mainly, on the studies on school culture, especially the works of Chervel (1990, 1998) and Julia (2001). The results of the research indicate that, with the establishment of graded school, new representations and expectation on student learning were built, that is, what the student should know to be promoted, or not, to the subsequent year, as well as to be approved, or reproved, in the final exams. With the creation of grupos escolares, there was a physical separation of students by school grades, and a more systematic regulation of a learning time, with a Teaching Program separated by semesters, which should be followed by teachers in each school period. The document analysis showed the complexity of the phenomena, making it impossible to point to a sole cause to their occurrence. Among the reasons for failure and retention, there were the long Teaching Program, students young age, and their low achievement. This work showed that, initially, the retention was not seen as an educational problem, getting new contours around the 1920s, when there is predominance, in the educational discourse, of psychology-based knowledge. To understand how, throughout the history of graded school, school failure and retention were naturalized and incorporated to school model has helped to reflect and problematize an issue that is still relevant nowadays.